IMPROVING STUDENTSâ€™ PROCESS IN WRITING PROCEDURE TEXT BY USING PICTURE SERIES - Andaresta, Kasih; Sutapa, Y. Gatot; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe present research was an attempt to know the improvement of teaching by using picture series on studentsâ€™ process in writing procedure text in Year-7 of â€œSMP Negeri 3 Sungai Rayaâ€ in the Academic Year of 2017/2018. The method used in this research is Classroom Action Research. This research was done in three cycles. The participants of this research were the seventh-grade English teacher and 32 students in class VII A. The researcher found that the picture series improved studentsâ€™ process in writing procedure text. Then the ideas were also clearly stated and the sentences were organized well. The students also began to show their interests by actively answered the questions and enthusiasm during the class activity until the end. The result of this study showed that the picture series did not only improve studentsâ€™ process in writing procedure text but also motivated the students to write in groups and individual.Keywords: Procedure Text, Picture Series Â  Â  Â